Hajj Service User Feedback Information System at The Office of The Ministry of Religion of The Deli Serdang District Based on Web - Syahputri, Rifdah; Kartika Dewi, Aulia (Jurnal Media Teknik Elektro dan Komputer, 2024)
Quality Hajj services are essential to the pilgrims' experience, and feedback management is one way to improve that quality. This research was conducted at the Hajj Section of the Office of the Ministry of Religious Affairs of Deli Serdang Regency, which faces obstacles in monitoring and evaluating services due to the absence of a structured system for managing pilgrims' feedback. The purpose of this research is to design a web-based information system that is effective in collecting, processing, and analyzing pilgrims' feedback to improve Hajj services. The technologies used include PHP as the application development platform and MySQL as the database. Data were obtained through surveys and interviews with service users, then tested on 50 users. The results showed that the system increased user satisfaction by 30% based on pre- and post-implementation indicators. The information system provides real-time analytical reports, makes it easier for staff to identify problems, and improves service responsiveness and transparency. Initial implementation at the Deli Serdang District Office of the Ministry of Religious Affairs demonstrated the system's effectiveness in supporting the evaluation and improvement of Hajj services. This study concludes that the implementation of a feedback information system can significantly improve the quality of Hajj services and has the potential to be implemented in other Ministry of Religious Affairs offices to support the improvement of service quality nationally.